ANALYSIS OF GESTATIONAL AGE FACTORS WITH NEONATAL ASPHYXIA LEVELS IN NEWBORN BABIES IN THE NUSA INDAH ROOM AT NGANJUK REGIONAL HOSPITAL - Puji Astutik (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Asphyxia neonatorum is a newborn emergency in the form of respiratory depression that continues, causing various complications. Neonatal asphyxia is caused by several factors, namely, intrauterine factors (mother's condition factors, uterine factors, placental factors, umbilical cord factors and fetal factors), gestational age factors and labor factors. This study aims to determine the factor analysis of gestational age and the level of neonatal asphyxia in the Nusa Indah Room at Nganjuk Regional Hospital. The research design uses a correlational design with a retrospective approach, this research was carried out on June 1 2023 in the Nusa Indah Room, Nganjuk Hospital. The population in this study was all 68 newborn babies. The sample was taken using a total sampling technique with a total of 68 respondents. The independent variable is the gestational age factor, the dependent variable is the level of neonatal asphyxia. The data collection instrument uses medical record data and statistical tests use the Contingency Coefficient with α = 0.05. The results of this study showed that almost half had a premature gestational age, namely 33 respondents (48.5%). Experiencing moderate asphyxia was 32 respondents (47.1%). And the results of the Coefficient Contingency test show p-value = 0.000 ≤ α (0.05), so Ha is accepted and Ho is rejected, which means there is a relationship between gestational age and the level of neonatal asphyxia in the Nusa Indah Room at Nganjuk Regional Hospital. Newborn babies with a history of premature gestational age are at risk of experiencing neonatal asphyxia. Nurses as implementers of curative measures are required to carry out nursing care appropriately to provide optimal assistance so that the incidence of neonatal asphyxia can be minimized